Design and analysis of the composite lattice frame of a spacecraft solar array - Morozov, E.V.; Lopatin, A.V. (Composite structures, 2011)
A novel design of the composite structural lattice frame for the spacecraft solar arrays is presented in the paper. The frame is composed of two flat lattice composite plates assembled into the three-dimensional panel using frame-like connectors. Design, fabrication, modelling and modal analysis of the panel solar arrays based on the proposed technology are discussed. The lattice panels are modelled as three-dimensional frame structures composed of beam elements subjected to the tension/compression, bending and torsion using the specialised finite-element model generator/design modeller. Results of the calculations of the frequencies and vibration forms for the lattice panels with various types of supports imitating the ways the panels can be attached to the spacecraft body, deployment must, and adjacent solar panels are presented and discussed. The lattice frame design for maximum fundamental frequency is performed subject to constraints imposed on the geometrical parameters of the solar panel.